V892 Tau: A Tidally Perturbed Circumbinary Disc in a Triple Stellar System - Miley, J (EDP Sciences, 2024)
Context. V892 Tau is a young binary star surrounded by a circumbinary disc that shows hints of an interaction with the low-mass nearby star V892 Tau NE. Aims. The goal of this paper is to constrain the orbit of V892 Tau NE and to determine the resulting circumbinary disc dynamics. Methods. We present new ALMA observations of the V892 Tau circumbinary disc at a twice higher angular and spectral resolution. We modelled the data with V892 Tau as a triple system and performed a grid of hydrodynamical simulations testing several orbits of the companion. The simulation outputs were then post-processed to build synthetic maps that we compared to the observations. Results. The 12CO emission of the disc shows clear non-Keplerian features such as spiral arms. When comparing the data with our synthetic observations, we interpreted these features as ongoing interactions with the companion. Our simulations indicate that an eccentricity of e ∼ 0.5 of the companion is needed to reproduce the observed disc extent and that a mutual inclination of ∆i ∼ 60◦ with the inner binary reproduces the measured disc tilt. Conclusions. In order to explain most of the features of the circumbinary disc, we propose that V892 Tau NE follows an orbit with a mild eccentricity 0.2 < e < 0.5 and a mutual inclination of 30◦ < ∆i < 60◦. Such a misaligned companion suggests the disc is oscillating and precessing with time, stabilising in an intermediate plane with a non-zero mutual inclination with the inner binary. Given the orbital configuration, we show that the stability of future planets is compromised in the second half of the disc once the gas has dissipated. © The Authors 2024.